Broadband noise prediction of a counter rotating open rotor based on LES simulation with phase-lagged assumption (draft). (8th December 2021) - Fiore, M.; Daroukh, M.; Montagnac, M.
Abstract: This paper presents the broadband noise analysis of a Counter Rotating Open Rotor (CROR) configuration. The numerical study is based on a hybrid approach: a Large Eddy Simulation (LES) code solves the near-flow field of the CROR configuration and the near-to-far-field propagation is then predicted by a Ffowcs Williams–Hawkings analogy either based on a solid or porous formulation. The LES solver uses a phase-lagged assumption with a proper orthogonal decomposition for the data storage. The numerical approach is validated against wind tunnel experimental data of a CROR configuration (AI-PX7) at three different operating points focused on the broadband noise. The analysis of the numerical simulations shows the predominant effect of the rear rotor suction side on the radiated broadband noise with an increasing contribution with span location. This source is related to the impingement of front rotor wakes and the development of leading edge vortices that induce large pressure fluctuations close to the leading edge on the suction side. Highlights: The LES with phase-lagged assumption accurately predicts the broadband noise of CROR. The broadband noise is predominantly radiated towards the forward polar arc region. The leading edge vortex on the rear rotor suction side contributes to broadband noise.